2019
DOI: 10.1001/jamanetworkopen.2019.0634
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Postdischarge Mortality Among Black and White Patients 65 Years and Older in the Medicare Hospital Readmissions Reduction Program

Abstract: Key Points Question In the Medicare Hospital Readmissions Reduction Program, did mortality from all causes increase during the 30 days after hospital discharge among black vs white patients 65 years and older? Findings In a cohort study using a time-series analysis including 3263 acute care hospitals, short-term mortality decreased more among black patients than white patients with acute myocardial infarction. Mortality increased among white patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Other studies using national Medicare data have focused on temporal trends in subgroups of hospitals and patients and are, therefore, not directly comparable to the above studies focusing on overall trends 3031. Finally, an analysis using 100 000 hospital admissions among Medicare beneficiaries in a quality improvement registry drawn from 500 US hospitals, which captured an inconceivably low two admissions for heart failure on average per hospital per month, did not replicate the secular trends in heart failure readmissions or mortality nationally 2232.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies using national Medicare data have focused on temporal trends in subgroups of hospitals and patients and are, therefore, not directly comparable to the above studies focusing on overall trends 3031. Finally, an analysis using 100 000 hospital admissions among Medicare beneficiaries in a quality improvement registry drawn from 500 US hospitals, which captured an inconceivably low two admissions for heart failure on average per hospital per month, did not replicate the secular trends in heart failure readmissions or mortality nationally 2232.…”
Section: Discussionmentioning
confidence: 89%
“…However, several independent analyses have found that the implementation of the HRRP was associated with an increase in post-discharge mortality at 30 days among patients admitted for heart failure and pneumonia compared with pre-HRRP trends (pre-2010), and that this increase was concentrated entirely among patients not readmitted after discharge. 6 17 18 19 Whether intensified efforts to manage returning patients in emergency departments and observation units explain increases in mortality observed in the years that preceded our study period is an important area for further research, given that this potential mechanism could explain increased mortality under the HRRP. 20 21 22 23 24 …”
Section: Discussionmentioning
confidence: 98%
“…Earlier work has explored the potential for unintended harms to patients resulting from the HRRP, with mixed findings, reflecting different study designs and model specifications. [38][39][40][41][42] A 2018 study by Wadhera et al 39 observed an increase in 30-day mortality, which was likely driven by patients not readmitted within 30 days of discharge. Our study found that the HRRP was associated with a 1.2% decrease in the likelihood of readmission when recently discharged patients presented to the ED with conditions for which admission is potentially nondiscretionary, particularly CHF.…”
Section: Discussionmentioning
confidence: 99%